MODERN DIRECTIONS AND RESEARCH METHODS IN ATHLETICS: A LITERATURE REVIEW (Physical Culture and Sport: Scientific Perspective, 2025)
Modern athletics is one of the most advanced sports disciplines, integrating achievements from various scientific fields to enhance training efficiency, prevent injuries, and improve recovery methods for athletes. In today's context, the use of technological innovations, artificial intelligence, and digital analysis methods has become particularly important for optimizing sports training. At the same time, there remains a need for a comprehensive review of current scientific trends and the identification of promising research directions in athletics.  The aim of this study is to identify key areas of research in athletics and to systematize them. To achieve this goal, an analysis of scientific and methodological literature was conducted, covering the main research trends in athletics in recent years. Six key research areas were identified: interdisciplinary approaches in sports science, technological innovations, injury prevention, sports training, recovery and nutrition, as well as future research perspectives.  The results of the study show that modern sports science actively implements cutting-edge technologies, including artificial intelligence, biomechanical analysis, and sensor devices, which allow for the personalization of training programs and increased training efficiency. Injury prevention research is particularly important, contributing to the development of individualized rehabilitation programs and optimization of the training process. Additionally, genetic research remains relevant, as it may serve as the foundation for new approaches to athlete selection and preparation. The conducted analysis outlines key trends and future perspectives for the development of sports science in the context of athletics. There has also been a growing interest in genetic research, ethical issues and the development of women's sports which opens up new perspectives for sports science.
Keywords: athletics; research; methods; analysis; technologies; training process